Manajemen Pemeliharaan Sarana UKS di SMA YPI Tunas Bangsa Palembang - Maria Assumpta Wikantari; Muh. Arfah; Muhammad Imanuddin; Muhammad Guntur; Afif Alfiyanto; Ivan Riyadi; Fitri Hidayati (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the maintenance of school health facilities at YPI Tunas Bangsa High School Palembang, as well as to determine the supporting and inhibiting factors. This type of research is descriptive with a qualitative approach. The key informants in this study were the person in charge of the School Health and the supporting informants was the deputy principal of the school's facilities and infrastructure sector, teachers, and school documents/archives related to the problems studied. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman analysis model. The results of this study indicate that the maintenance of School Health facilities is carried out through 1) Maintenance of School Health facilities can be said to be quite good, it can be seen from the people who use School Health facilities, they always try to be responsible for maintaining School Health facilities; 2) Supporting factors for maintaining School Health, namely a) School Health staff and students making good use of the facilities; b) the maintenance schedule is by the schedule of the School Health officers; and c) two cupboards are available to store School Health facilities; 3) The inhibiting factors are a) not having a special room for storage of School Health facilities, and b) not using a special record book for the maintenance of School Health facilities so that the maintenance process is less than optimal.